Pengaruh Pelayanan Administrasi Terhadap Tingkat Kepuasan Masyarakat di KUA Kecamatan Sanana - Rifani Gorontalo Rifani (Al-Mizan: Jurnal Kajian Hukum dan Ekonomi, 2024)
Administrative services are services in the form of providing various forms of documents needed by the community. One example of a marriage registration service. Community satisfaction is the community's response to the discrepancy between the previous level of interest and the actual performance they perceive. The aim of the research is to determine administrative services at the Sanana District religious affairs office (KUA) and to determine the level of public satisfaction at the Sanana District religious affairs office (KUA). The method used in this research is quantitative research, using Population and Sample where the research population includes all data related to services. Meanwhile, the research sample includes consumer satisfaction data at the Sanana District Religious Affairs Office (KUA). The results of the research, partially or t-test, are that the Service Quality variable has a positive and significant effect on the Community Satisfaction variable as indicated by the significant value of 0.000, which is smaller than 0.05 with the t test value showing 4.771. This means that the administrative service variable has a significant effect on community satisfaction in KUA Sanana District. Keywords: Influence of Service, Community Satisfaction, administration